2017
DOI: 10.1155/2017/3860107
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Clear Cell Adenofibroma of the Ovary

Abstract: Borderline clear cell tumors are extremely rare, and few cases have been reported in the literature. Herein, we present a case of borderline clear cell adenofibroma of the ovary in a 58-year-old woman who presented with a pelvic mass and constipation. Physical examination revealed a 10 cm solid midline pelvic mass. Computed tomography showed an 8 cm heterogeneous enhancing mass attached to the left posterolateral wall of the uterus. The patient's serum CA 125 levels were slightly elevated (80.9 U/ml). The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Although endometriosis has been implicated as a precursor for certain types of epithelial ovarian cancer [7,8], the occurrence of ascites secondary to endometriosis is rarely encountered, particularly among Asian women. This entity simulates gynecological malignancy and is seldom recognized before surgical exploration of the abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Although endometriosis has been implicated as a precursor for certain types of epithelial ovarian cancer [7,8], the occurrence of ascites secondary to endometriosis is rarely encountered, particularly among Asian women. This entity simulates gynecological malignancy and is seldom recognized before surgical exploration of the abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CCBT was regarded as deriving from only clear cell adenofibroma in the adenofibromatous pathway. In previous reports, 95.1% of cases with CCBT coexisted fibromatous component (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). However, in case 1 in our case, CCBT was considered to develop from endometriosis because CCBT was adjacent to atypical endometriosis and endometriosis.…”
Section: Discussionmentioning
confidence: 56%
“…A review of literature of CCBT with and without fibromatous component including our study were demonstrated in Table II (8,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). There were 81 cases with CCBT; 77 cases (95.1%) with fibromatous component and 4 cases (4.9%) without fibromatous component.…”
Section: Discussionmentioning
confidence: 78%
“…However, in the case series of this review, we failed to find a prevalent fibrosis pattern within the AWE; interestingly, we reported the first case in the literature of BCCT growth on AWE, that support this hypothesis. These types of lesions represent less than 1% of ovarian borderline tumors and little is known about the mechanisms involved in the neoplastic progression of this entity 67 . When occurs, tumor arises from AWE become a challenge for both surgical and medical management.…”
Section: Discussionmentioning
confidence: 99%